Only a cowboy will do - Pine, A. J.; Curtis, Melinda (Romance fiction writer) (Pine, A. J. Meadow Valley., 2021)
While staying at the Meadow Valley Guest Ranch, Jenna Owens, who is always caring for others, decides to put herself first for a change with the help of her psychic chicken and one of the owners of the ranch--Colt Morgan.